2013
DOI: 10.1155/2013/697972
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes, Peripheral Blood Mononuclear Cells, and THP-1 Cells Exhibit Different Cytokine Expression Patterns following Stimulation with Lipopolysaccharide

Abstract: THP-1 cells are widely applied to mimic monocytes in cell culture models. In this study, we compared the cytokine release from THP-1, peripheral blood mononuclear cells (PBMC), monocytes, or whole blood after stimulation with lipopolysaccharide (LPS) and investigated the consequences of different cytokine profiles on human umbilical vein endothelial cell (HUVEC) activation. While Pseudomonas aeruginosa-stimulated (10 ng/mL) THP-1 secreted similar amounts of tumor necrosis factor alpha (TNF-α) as monocytes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
162
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(188 citation statements)
references
References 28 publications
20
162
5
1
Order By: Relevance
“…In addition, we determined that the genotypes 1, 2, 3, and 4 had stimulated the secretion of IL-1β, IL-6, TNF-α, and IL-10 with different levels. Thus, our findings were similar with the previous studies (10,14,33,39,41,42).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, we determined that the genotypes 1, 2, 3, and 4 had stimulated the secretion of IL-1β, IL-6, TNF-α, and IL-10 with different levels. Thus, our findings were similar with the previous studies (10,14,33,39,41,42).…”
Section: Discussionsupporting
confidence: 93%
“…alike transcriptional pattern as peripheral blood mononuclear cells derived macrophages (13)(14)(15)(16)(17). In addition, HL-60 cells can differentiate into neutrophils in response to various stimuli like dimethyl sulfoxide, retinoic acid, and dibutyryl cyclic adenosine monophosphate (Bt 2 -cAMP).…”
Section: Original Articlementioning
confidence: 99%
“…Therefore, we investigated whether glycer-AGEs can also stimulate inflammatory mediators in ECs and human peripheral blood mononuclear cells (PBMCs) isolated from healthy donors. THP-1 and PBMCs showed comparable responses to inflammatory mediators such as TNF-a and IL-1b (Schildberger et al 2013). Our findings show that glycer-AGEs clearly invoke the expression of inflammatory cytokines in HUVECs cultured with both THP-1 cells and PBMCs ( Figure S2(A)), and treatment of PBMCs with glycer-AGEs released TNF-a and IL1b to an even greater extent than did THP-1.…”
Section: Discussionmentioning
confidence: 53%
“…Several reports have shown that the interaction between THP-1 and ECs is comparable to that between human primary monocytes and ECs (Kaplanski et al 1998;Schildberger et al 2013). However, THP-1 cells do not completely represent the phenotype of blood monocytes.…”
Section: Discussionmentioning
confidence: 96%
“…THP-1 cells are also an attractive model system for inflammasome activation, as they allow the development of stable cell lines in which specific inflammasome components are knocked down. However, THP-1 cells are not a perfect model of primary human monocytes, demonstrating some differences in cytokine profiles in response to stimuli (35,36).…”
Section: Resultsmentioning
confidence: 99%